032 Can a massive open online course (MOOC) inform concussion prevention knowledge translation?. (3rd March 2020) - Adams, Stephanie; Fremont, Pierre; Lock, Jennifer; Yeates, Keith O; Emery, Carolyn; Reid, Leslie; Werthner, Penny; Schneider, Kathryn
Abstract : Background: To reduce the burden of concussion, effective prevention strategies are required. These should: 1) focus on primary prevention in addition to secondary prevention of recurrence and 2) promote global engagement. A Massive Open Online Course (MOOC) on concussion allows stakeholders to interact with experts while learning about the latest evidence and resources on concussion prevention, and may contribute to enhancing awareness and knowledge of prevention. Objective: To evaluate the feasibility and effectiveness of a MOOC, which includes a focus on concussion prevention, as a global knowledge translation (KT) strategy with multiple stakeholders. Design: De-identified learning analytics were used to assess participation, completion rates, and knowledge gains. Setting: Worldwide web. Participants: Data from 8591 self-registered learners (e.g., health professionals, coaches, sports organisations, athletes, parents, teachers, school administrators) was analysed. Intervention: The MOOC was available for 9 weeks and included six modules: introduction to concussion, primary prevention, detection (secondary prevention), management, treatment (tertiary prevention) and implementation/revision of protocols. Each module featured interactive learning content/materials and a reflective process supporting KT and evaluations (for more: https://www.ucalgary.ca/knes/online-concussion-course ). Main outcome measurements: Number of registered learners accessing and completing each module; post-module exam scores; pre-test and post-course exam scores. Results: Of 8591 people who registered, 3093 (36%) successfully completed all evaluations. The modules were highly accessed by participants [introduction=5161 (60%), prevention=4287 (50%), detection=3733 (43%), management=3388 (39%), treatment=3223 (38%), protocols=3068 (36%)]. The prevention module had the highest mean post-module exam score 92.06% [95% CI; 91.76–92.36)]. There was a 12% increase in overall knowledge between pre- and post-course exam scores (mean score increased from 67% to 79%). Conclusions: The sustained engagement of the participants suggests that a MOOC on concussion may be an effective and globally accessible KT approach. The MOOC also successfully combined primary prevention with more traditional secondary and tertiary concussion prevention foci, thereby enhancing programming that aims to improve concussion literacy.